The clinical features and prognostic outcomes of primary mediastinal yolk sac tumors: A retrospective analysis of 15 rare cases from multiple centers. Issue 29 (23rd July 2021) - Qin, Li; Zhu, Menglin; Wang, Tiejun; Wang, Hongli; Pan, Qin; He, Du
Abstract : Abstract: Primary mediastinal yolk sac tumors (PMYSTs) are a rare occurrence. As such, the clinicopathological features, treatment, and prognosis, of this disease still remain unclear. In this study, we aimed to provide further information relating to this rare malignancy in order to facilitate the creation of more specific clinical guidelines for the diagnosis and treatment of patients with PMYSTs. In this retrospective study, we recruited 15 patients who had been diagnosed with PMYST from four medical institutions to create a population-based cohort. We then used Kaplan-Meier analysis and the log-rank test to investigate and compare overall survival (OS) and progression-free survival (PFS). A total of 15 cases were identified. The mean age was 27.3 years (range: 19–34 years). The estimated 1- and 2-year PFS rates were 66.7% and 60.0%, respectively. The 1- and 2-year OS rates were both 73.3%. Computer tomography scans revealed tumors were located in the anterior middle mediastinum (5 cases), the anterior superior mediastinum (1 case), the left anterior mediastinum (3 cases), and the right anterior mediastinum (6 cases). Of the 15 patients receiving extended resections, the majority (40.0%) underwent tumor resection, partial pericardiotomy, pulmonary wedge resection, and mediastinal lymphadenectomy. R0 resections were achieved in eleven patients. Four patients underwent R2 resection and experienced postoperative complications, including pneumonia (2 cases), atelectasis (1 case), and bronchopleural fistula (1 case). Four patients developed postoperative lung metastasis. Three patients died due to progressive diseases. Disease recurred in all patients at a median of 8.0 months (range: 6.0–11.0 months). PMYST is a rare but highly malignant tumor with a poor prognosis. Tumor resection, with optimal extended surgical management, may provide patients with the best chance of a cure although postoperative complications relating to the pulmonary systems should be treated with caution. Abstract : Supplemental Digital Content is available in the text